Le Grand Nord : un modèle pour les Alpes au XVIIIe siècle ? - Guyot, Alain (Presses universitaires de Rennes, 2019)
In the second half of the eighteenth century, the fad for the Alps and in particular for Mont Blanc started a fashion for travelling from which stories would be written and which were amongst the first to describe a world where only a few men had yet dared venture: the high mountain peaks. However, in order to describe the emotions aroused by this unusual spectacle, travellers to Switzerland or Savoy often had recourse to make comparisons with another environment which was not necessarily better known: this environment would later be called the Far North, whether it was called Greenland, Spitzberg or New Zemble (‘New Earth’) before. Why did the first descriptive writers about the Alps frequently have recourse to this “Northern model”? More than a reference point enabling us to understand a neglected landscape, the Far North was rather a representation of a “fantasy machine” inspired by the traditional myth of Thule and alluring readers who were eager for powerful experiences on their doorstep.